New poetry, young poetry or contemporary poetry? A field of dilemmas, tension, and ambivalences in Costa Rican literary criticismand historiography - Arroyo-Carvajal, Yordan (2023)
This research presents a metacritical and epistemological analysis, from literary criticism and historiography, around the framework of tensions generated on the ambivalent process of formation of an “emerging generation” or “new generation”. This causes a minefield ready for analysis that starts, as the main study, from the Anthology of Young Poetry. New Costa Rican Poetry (2020), where some of its poems are analyzed. There is a framework of dilemmas and ambivalences based on ages and labels such as: “young poetry”, “new generation”, “chrysalis generation” and “emerging generation”. In this regard, dates and places of birth were placed, plus a database added in the final notes of this work, with the aim of providing information to future researchers and people interested in this topic. Finally, it is defended, by the way of final considerationsopen to more dialogues, how the attempt to create a “new generation”, taking the Anthology of Young Poetry. New Costa Rican Poetry (2020) as abridge, is not the recommended path to direct a north in current Costa Rican poetry, since the exchange in poetic paradigms is not a matter of ages, but epistemological, just where, responding to the criteria of Zavala (2007 and 2008), we call for groups of researchers committed to following up on this topic.